Post-weaning performance of calves as affected by longstem hay and pre-weaning creep feeding - G. Greathouse; E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1970)
Mortality in calves at weaning is one of the major problems in the beef industry. Some relief from this problem might be achieved if the calves could be changed from milk and grass to high energy ration with little lapse in time. Many ranchers do not have adequate equipment, labor or time to do this job on the ranch where it could best be done. If a post-weaning management system could be formulated that would be acceptable to the producers of the calves and reduce death and sickness it would be of tremendous benefit. Many local feed companies are in a position to deliver complete rations to a self-feeder in the owner's lot. The management system proposed here would enable the rancher to use this service.
Keywords: Cattlemen& #x27; s Day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station); 536; Beef; Performance; Longstem hay; Creep feeding